2021
DOI: 10.1111/bcp.15104
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of prediction tools to identify adult hospitalized patients at risk of drug‐related problems: A systematic review of clinical prediction models and risk assessment tools

Abstract: This study aimed to review systematically all available prediction tools identifying adult hospitalized patients at risk of drug-related problems, and to synthesize the evidence on performance and clinical usefulness.Methods: PubMed, Scopus, Web of Science, Embase, and CINAHL databases were searched for relevant studies. Titles, abstracts and full-text studies were sequentially screened for inclusion by two independent reviewers. The Prediction Model Risk of Bias Assessment Tool (PROBAST) and the Revised Quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
(465 reference statements)
2
6
0
Order By: Relevance
“…It also argues for caution when interpreting negative findings for risk factors. In correspondence with the findings of previous reviews evaluating the performance of predictive scoring tools, this supports the common conception that some risk factors and predictive scoring tools at this stage may not be transferrable to more diverse settings [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It also argues for caution when interpreting negative findings for risk factors. In correspondence with the findings of previous reviews evaluating the performance of predictive scoring tools, this supports the common conception that some risk factors and predictive scoring tools at this stage may not be transferrable to more diverse settings [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 86%
“…There is a great clinical need for the improved identification of patients at risk for DRP. The numerous predictive scoring tools proposed, so far, have already been the topic of excellent reviews [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ], but to the best of our knowledge this is the first systematic review and analysis of scoring tools with a focus on the individual factors included in the tools. The heterogenicity previously noted at the level of the overall predictive scoring tools is matched by a comparable variability of individual risk factors as well as definitions of risk factors and thresholds of risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, no consensus was reached on which patients should (at least) be targeted by IPS due to their risk of medication-related harm. Our findings support those of the recent systematic review by Deawjaroen et al 54 The authors identified 14 currently available prediction tools and assessed their clinical utility in identifying adult hospitalised patients at risk of medication-related harm. Interestingly, the authors concluded that none of the tools were optimal for this purpose.…”
Section: Future Considerations and Researchsupporting
confidence: 89%
“…[21][22][23] Cautious analysis of these data using both conventional and newer prediction tools can be helpful. [24][25][26] Similarly, the development of newer, easily portable equipment has raised new possibilities for the collection of standardized data. 27 We need to study large patient cohorts over time or in larger geographical territories to draw clinically relevant conclusions.…”
mentioning
confidence: 99%